Design and parameter optimization of PBC-NDO composite controller for electric vehicle wireless charging system - YAN Rongge; YAN Chunjiao; YANG Qingxin; ZHANG Xian (Diance yu yibiao)
Aiming at the problems that the charging voltage of the wireless charging system of electric vehicle is unstable due to the offset of the primary and secondary coils and load fluctuation in the process of variable voltage intermittent fast charging, and the controller parameters are mostly selected by empirical value and trial and error method, a composite control strategy combining passivity based controller (PBC) and nonlinear disturbance observer (NDO) based on particle swarm optimization algorithm is proposed. A passivity based controller considering interference compensation is designed for the secondary DC-DC converter of wireless power transfer (WPT) system. The nonlinear interference observer is introduced to estimate the interference, and the interference estimation value is combined with the passivity based controller to design a PBC-NDO composite controller suitable for variable voltage intermittent wireless charging system of electric vehicles. Particle swarm optimization algorithm is used to optimize the parameters of the composite controller to further improve the anti-interference performance and dynamic response performance of the controller. The effectiveness of the proposed method is verified by simulation and experiments. The experimental results show that the composite controller has strong anti-interference and dynamic response, the maximum steady-state error offset rate in the charging stage is 2%, and the dynamic response time is controlled within 0.6 ms.